Sports and energy drink consumption are linked to health-risk behaviours among young adults - Larson, Nicole (Public Health Nutr, 2015)
OBJECTIVE: National data for the USA show increases in sports and energy drink consumption over the past decade with the largest increases among young adults aged 20–34 years. The present study aimed to identify sociodemographic factors and health-risk behaviours associated with sports and energy drink consumption among young adults. DESIGN: Cross-sectional analysis of survey data from the third wave of a cohort study (Project EAT-III: Eating and Activity in Teens and Young Adults). Regression models stratified on gender and adjusted for sociodemographic characteristics were used to examine associations of sports and energy drink consumption with eating behaviours, physical activity, media use, weight-control behaviours, sleep patterns and substance use. SETTING: Participants completed baseline surveys in 1998–1999 as students at public secondary schools in Minneapolis/St. Paul, Minnesota, USA and the EAT-III surveys online or by mail in 2008–2009. SUBJECTS: The sample consisted of 2287 participants (55 % female, mean age 25·3 years). RESULTS: Results showed 31·0 % of young adults consumed sports drinks and 18·8 % consumed energy drinks at least weekly. Among men and women, sports drink consumption was associated with higher sugar-sweetened soda and fruit juice intake, video game use and use of muscle-enhancing substances like creatine (P≤0·01). Energy drink consumption was associated with lower breakfast frequency and higher sugar-sweetened soda intake, video game use, use of unhealthy weight-control behaviours, trouble sleeping and substance use among men and women (P<0·05). CONCLUSIONS: Health professionals should consider the clustering of sports and energy drink consumption with other unhealthy behaviours in the design of programmes and services for young adults.